Arborização urbana: relação entre as espécies arbóreas e o sistema viário: uma análise em Patos de Minas, MG - Araújo, Eduardo Cardoso de (2020)
Urban afforestation plays a key role in the urban planning process. It must be considered, along with other elements, in an integrated way in the landscape and is conceptually present in the road system. It is an element capable of providing several environmental, functional and aesthetic benefits. Its application requires studies that can contribute to its proper use in urban spaces, which are so complex and fragmented. The present work aims to analyse how afforestation relates to different types of roads and their urban elements to propose criteria that can help in the planning and consequent improvement of the public space. The work uses the city of Patos de Minas, MG to carry out the research. The collection of data through bibliographic information and public agencies made it possible to deepen this research on the present theme. Field studies and urban readings of the analyzed roads were essential to relate the researched data and, as a result, to develop instruments and guidelines for the application of afforestation in these spaces. The results obtained with this research offer information that may allow, with the support of public agencies and society in general, conditions to observe, care for and plan afforestation in urban spaces.